2015
DOI: 10.1016/j.neuropharm.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 regulation of synaptic function in the CNS

Abstract: A growing body of evidence supports a role for glial-produced neuroimmune factors, including the cytokine IL-6, in CNS physiology and pathology. CNS expression of IL-6 has been documented in the normal CNS at low levels and at elevated levels in several neurodegenerative or psychiatric disease states as well as in CNS infection and injury. The altered CNS function associated with these conditions raises the possibility that IL-6 has neuronal or synaptic actions. Studies in in vitro and in vivo models confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 176 publications
(235 reference statements)
5
132
1
3
Order By: Relevance
“…However, we did not observe any difference in the activation of glial cells in the retina after IL-6 treatment, suggesting a direct effect on ganglion cell activity. In accordance with this idea, it was previously shown that IL-6 decreases N-methyl- D- aspartate activity, weakening synaptic transmission [8,47]. Thus, it is reasonable to propose that IL-6 decreases retinal glutamatergic input to the SC favoring axonal sprouting of the opposite, nontreated eye.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, we did not observe any difference in the activation of glial cells in the retina after IL-6 treatment, suggesting a direct effect on ganglion cell activity. In accordance with this idea, it was previously shown that IL-6 decreases N-methyl- D- aspartate activity, weakening synaptic transmission [8,47]. Thus, it is reasonable to propose that IL-6 decreases retinal glutamatergic input to the SC favoring axonal sprouting of the opposite, nontreated eye.…”
Section: Discussionmentioning
confidence: 66%
“…This interleukin increases the survival of retinal ganglion cells (RGCs) in culture [3,4,5] and also in an in vivo model of elevated ocular pressure [6,7]. Other studies have associated IL-6 to synaptic plasticity since endogenous IL-6 inhibition can prolong long-term potentiation and improve memory [8,9,10,11]. Also, IL-6 modulates both excitatory and inhibitory synapses and reduces paired-pulse inhibition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the ensuing immunological and metabolic disturbances in the body exert strong feedback effects on cerebral circuits. For example, stress-related increases in levels of cortisol and pro-inflammatory cytokines affect NMDA receptor (NMDAR) function (Nair and Bonneau, 2006; Gruol, 2015; Vezzani and Viviani, 2015). Importantly, NMDAR dependent signaling is thought to be essential for updating and encoding representations of beliefs (Corlett et al, 2010; Vinckier et al, 2016).…”
Section: The Need For a Computational Theory Of Fatiguementioning
confidence: 99%
“…The acute IL-6 would presumably activate IL-6Rs on nearby cells and cause functional changes through downstream signaling. IL-6Rs are expressed on several cell types in the hippocampus, including neurons and glia (Gruol, 2014). To assess this possibility we carried out two types of experiment: (a) we measured by ELISA the levels of IL-6 in a separate group of IL-6 tg and non-tg hippocampal slices treated with control saline (ACSF) or 60 mM ethanol for 30 min, and (b) we measured the relative level of activation of downstream signal transduction molecules activated by IL-6.…”
Section: Resultsmentioning
confidence: 99%